Winemaking, Environmental Impacts and Sustainability: New Pathways from Vineyard to Glass? - Pires Vieira da Rocha, Carla; Nodari, Eunice Sueli (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2020)
In this text we explore the relationship between vitiviniculture and environment, observing the current conjuncture in which environmental problems are worsening. Taking as a baseline a survey of the literature and as a time frame the 1970s to the present, we begin by examining the development of vitiviniculture from the wider perspective of the contemporary global agrifood system, highlighting in particular the environmental impacts generated by this system. Next, taking into account the panorama of vitiviniculture in Brazil, we turn our focus to notions of sustainability with the aim of outlining possibilities for a reconfiguring of this issue and, at the same time, contextualizing the extent to which the country has been pursuing this direction. We conclude that the future of winemaking depends especially on a more harmonious intervention of human beings in the environment.